Encephalitis with convulsive status in an immunocompetent pediatric patient caused by Bartonella henselae - Polar, Rosario Cerpa (2016)
Cat scratch's disease caused by Bartonella henselae, is known to be a self-limited benign process in immunocompetent children. The association with neurologic manifestations is very uncommon especially in patient with no immunologic defects and in cases without specific treatment. A 7 years old male patient, without any immunocompromised defect, presented an atypic presentation of the cat scratch disease. The patient came to the hospital in two opportunities in a status epilepticus, in both cases the diagnosis was encephalitis by Bartonella henselae and the evolution with treatment was monitored with PCR (polymerase chain reaction) in cerebrospinal fluid and blood, as well as IFI (IgM, IgG) serology (indirect immunofluorescence). The patient had a favorable clinical and laboratory evolution for 6 months showing no recurrence of the disease.